Penggunaan Media Audiovisual untuk Meningkatkan Motivasi dan Hasil Belajar Materi Budidaya Tanaman Pangan pada Siswa Kelas X IPA 2 Sekolah Menengah Atas - Sugiono, Sugiono (Universitas Sebelas Maret, 2020)
he purpose of this study is 1) To find out the increase in student motivation byusing audiovisual media in class X students. 2) To find out the increase in student learningoutcomes using audiovisual media in class X.IPA 2 students of SMAN 2 Salatiga on thesubject matter of food crop cultivation in the Workshop and Entrepreneurship even semestersemester 2019/2020. The research subjects in this study are students of class X.IPA 2 SMAN 2Salatiga Pagentan, totaling 33 students. Methods of data collection by testing, observation,and documentation methods. Provision of action in the form of the use of audiovisual media tostudents of class X.IPA 2 of SMAN 2 Salatiga on the subject matter of food crop cultivation inthe Workshop and Entrepreneurship even semester semester 2019/2020 can improve studentmotivation and learning outcomes. Class X.IPA 2 High School 2 Salatiga students' motivationin the cultivation of food crops subject matter in the Workshop and Entrepreneurship in theeven semester of the 2019/2020 academic year only reached only a percentage of 62.37%,after being given an action it increased to 70.96% in the first cycle and in the cycle IIincreased to 81.57%. Student learning outcomes in class X.IPA 2 of SMAN 2 Salatiga on thesubject matter of food crop cultivation in the subjects of Entrepreneurship andEntrepreneurship in the even semester of the academic year 2019/2020.